Direct 3D printing of bilayered scaffold for subchondral plate regeneration - Torun, Sena Su; Bozdag, Mehmet Murat; Evran, Savas; Ilhan, Elif; Koyuncu, Ayse Ceren Calikoglu; Gunduz, Oguzhan; Ustundag, Cem Bulent (IOP Publishing Ltd, 2025)
Subchondral plate degeneration presents significant challenges in the treatment of osteochondral defects and requires innovative approaches for effective regeneration. The cooperative existence of multiple layer types with different characteristics makes it difficult to meet the mechanical and biochemical requirements of subchondral tissue. Direct Ink Writing (DIW) allows complex, structured scaffolds to be fabricated at room temperature while preserving material integrity and bioactivity. The aim of this study was to produce a bilayered scaffold based on poly(e-caprolactone), polyethylene glycol and hydroxyapatite that mimics the characteristics of subchondral bone and calcified cartilage in the native subchondral plate. Printability tests were performed to determine the optimal polymer concentration. The morphological and chemical properties of the 3D-printed scaffolds were analyzed using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The presence of hydroxyapatite was found to enhance the swelling and degradation properties of the scaffolds. Mechanical characterization revealed distinct tensile strength and stiffness gradients between the bone layer (BL) and the calcified cartilage layer (CCL). The BL exhibited a Young's modulus of 167.45 +/- 57.51 MPa and a tensile strength of 4.05 +/- 0.27 MPa. In contrast, the CCL showed a lower modulus of 21.95 +/- 0.43 MPa and a tensile strength of 2.33 +/- 0.25 MPa. These values align with the mechanical gradient of native tissue. Numerical analysis predicted the scaffold's behavior under compressive force. Furthermore, in vitro cell culture studies demonstrated biocompatibility, showing that all scaffolds were biocompatible with cell viability exceeding 83% after seven days. Overall, the developed bilayered, 3D-printed scaffolds could be a potential tissue-engineered solution for treating subchondral plate degeneration.
Keywords: 3D printing; direct ink writing; polycaprolactone; bilayered scaffold; subchondral plate; hydroxyapatite; IN-VITRO; TISSUE; FABRICATION; DEGRADATION; FIBER; PCL; Materials Science